Potensi Propolis Sebagai Imunomodulator Pada Tikus (Rattus norvegicus Berkenhout, 1769) Galur Wistar yang diinduksi Penisilin-G - Laksmindra Fitria; Onny Nurrahman Marwayana (Biogenesis: Jurnal Ilmiah Biologi, 2015)
Propolis is a honeybee product collected from plants sap. This resinous substance is used to build and maintain the nest. Propolis has long been declared as a safe material for health maintaining. The purpose of this research was to study the potential use of Propolis as an immunomodulator in Penicillin-G-induced Wistar rats. A total of 30 male rats aged 5 months with 200-240 grams body weight were divided into 6 groups: Control Placebo (im injection of aquabidest+oral administration of NaCl 0.9%); Control Penicillin (im injection of 21.6 mg Penicillin+oral administration of NaCl 0.9%); Control Propolis (im injection of aquabidest+oral administration of 27.0 mg Propolis); Treatment 1 (im injection of 21.6 mg Penicillin+oral administration of 13.5 mg Propolis); Treatment 2 (im injection of 21.6 mg Penicillin+oral administration of 27.0 mg Propolis); and Treatment 3 (im injection of 21.6 mg Penicillin+oral administration of 40.5 mg Propolis). Leukocytes profile (total and differential counts), body temperature, and urine acidity (pH) before and after treatment were determined as pretest and posttest data. Data were analyzed statistically using ANOVA followed by DMRT (p <0.05). Results showed that administration of Propolis significantly increased neutrophils count above the normal range (more than 4.41x103/L), whereas significantly decreased lymphocytes count below the normal range (less than 6.75x103/L). This causes the value of N/L ratio increased significantly. Administration of Penicillin and the combination with Propolis significantly increased body temperature (above 38C), while treatment with Propolis alone did not induce fever or inflammation (normal temperature 37-38C). Administration of Propolis reduced urine acidity due to the impact of the administration of Penicillin (pH 5.5-7.0). It can be concluded that oral administration of Propolis in Penicillin G-induced male Wistar rats exhibited immunosuppressive effect on lymphocytes. It was suggested as the role of Caffeic acid phenethyl ester (CAPE), the main bioactive compound in Propolis which also acts as an antiinflammatory agent. Further research is still needed to support this finding.Keywords: CAPE, immune system, immunomodulators, Penicillin, Propolis